The European Union Solidarity Fund: An Important Tool in the Recovery After Large-Scale Natural Disasters - Maria IONCICĂ; Eva-Cristina PETRESCU (Revista Română de Statistică, 2016)
This paper analyses the situation of the European Union Solidarity Fund, as an important tool in the recovery after large-scale natural disasters. In the last millennium, the European Union countries have faced climate change, which lead to events with disastrous consequences. There are several ex-post financial ways to respond to the challenges posed by large-scale natural disasters, among which EU Solidarity Fund, government funds, budget reallocation, donor assistance, domestic and/or external credit. The EU Solidarity Fund was created in 2002 after the massive floods from the Central Europe as the expression of the solidarity of EU countries. Romania has received financial assistance from the EU Solidarity Fund after the occurrence of major natural disasters, regional and neighbouring country disasters. The assessment of large-scale natural disasters in EU is very important and in order to analyse if there is a concentration of large-scale natural disasters in EU we used the Gini coefficient. In the paper, the method of the statistical analysis and the correlation between several indicators were used to study the financial impacts of large-scale natural disasters in Europe, and especially in Romania.